Semiotic space of the central housing of Yerevan State University: interior and exterior - Simyan, Tigran S. (Human in the Socio-Cultural Dimension, 2020)
The article considers the semiotized space of the interior and exterior of the central building of Yerevan State University. The description is carried out from interior to exterior. A special place is given to the lobby, the structure of the university’s museum, as well as the exterior. Cultural artifacts that refer to social, cultural and historical memory are revealed to the university’s «reader». The main semantic markers of the «center» of the university (museum, library and sculptures) are the carriers of cultural, national and supranational memory. The library shows the formation and history of the university, as well as the most important and dramatic events in the history of the Armenian people: the II World War, the Karabakh War of the 1990s and 2016, which are also accented and meaningful in the exterior university.